Pertumbuhan Dan Hasil Tanaman Selada Merah (Lactuca Sativa L.) Akibat Pemberian Beberapa Takaran Kascing - Hayati Nurul Haq; Rahmawati Rahmawati; Chika Sumbari (CULTIVATE: Journal of Agriculture Science, 2024)
Research in the form of a field experiment with the title "Growth and Yield of Red Lettuce Plants (Lactuca sativa L.) Due to Giving Several Doses of Vermicompost" was carried out in the agricultural garden of the Muhammadiyah West Sumatra Campus, Faculty of Agriculture, Tanjung Gadang Koto Nan Ampek District, West Payakumbuh District, Payakumbuh City which is located at an altitude of ±514 meters above sea level with Inseptisol soil type. The trial will start from May to July 2023. This research was carried out using a Randomized Block Design (RAK), where there were 5 treatments and 4 groups so that the total consisted of 20 experimental plots. Each plot contained 16 plants and 3 were sample plants chosen randomly. The plot size is 1 m x 1 m, with the treatment being the vermicompost dosage as follows. 0 tons/ha, 2 tons/ha, 4 tons/ha, 6 tons/ha, and 8 tons/ha. The observation parameters carried out were plant height (cm), number of leaves (pieces), length of the longest leaf blade (cm), width of the widest leaf blade (cm), wet weight per plant (g), wet weight per plot (kg), and wet weight per hectare (ton). Based on the results of the research experiments carried out, it can be concluded that giving several doses of vermicompost has not been able to increase the growth and yield of red lettuce plants. Based on the conclusions, it is recommended to carry out further experiments on red lettuce plants with different varieties with different doses of vermicompost.